Retrospective content analysis of consumer product reviews related to chronic pain - Fan, Jungwei W.; Wang, Wanjing; Huang, Ming; Liu, Hongfang; Hooten, W. Michael (Frontiers in Digital Health, 2023)
Chronic pain (CP) is pain that lasts for more than three months, causing prolonged physical and mental burden to the patients. According to the U.S. Centers for Disease Control and Prevention, CP contributes to more than five hundred billion U.S. dollars each year in direct medical costs plus the associated productivity loss. CP is complex in etiology and can occur anywhere in the body, making it difficult to treat and manage. There is a pressing need for research to better summarize the common health issues faced by consumers living with CP and their experience in accessing over the counter analgesics or therapeutic devices. Modern online shopping platforms offer a broad array of opportunities for the secondary use of consumer-generated data in CP research. In this study, we performed an exploratory data mining study that analyzed CP-related Amazon product reviews. Our descriptive analyses characterized the review language, the reviewed products, the representative topics, and the network of comorbidities mentioned in the reviews. The results indicated that most of the reviews were concise, yet rich in terms of representing the various health issues faced by people with CP. Despite the noise in the online reviews, we see potential in leveraging the data to capture certain consumer-reported outcomes or to identify shortcomings of the available products.